Characterization and applications of a monoclonal antibody against infectious salmon anaemia virus - Falk, K; Namork, E; Dannevig, B H (Diseases of aquatic organisms, 1998)
The preparation of the first monoclonal antibody (MAb) against the orthomyxovirus-like infectious salmon anaemia (ISA) virus is described. Characterization of the MAb included isotyping, enzyme-linked immunosorbent assay (ELISA), immunofluorescent staining of virus infected cell cultures (SHK-1 cells), immunoelectron microscopy (IEM) of negatively stained virus preparations, virus neutralization assay and haemagglutination inhibition assay. The MAb reacted with ISA virus preparations both with immunofluorescent staining and in ELISA. No reactions were observed in cell cultures infected with other viruses infecting salmonids including infectious pancreatic necrosis (IPN) virus, viral haemorrhagic septicaemia (VHS) virus and infectious haematopoietic necrosis (IHN) virus. The MAb was also shown to neutralize ISA virus infection in cell cultures and to inhibit the haemagglutination reaction. IEM demonstrated binding to the surface of negatively stained ISA virions. Thus, it is concluded that the MAb binds to the haemagglutinin on the virion surface. Furthermore, using immunofluorescent staining of virus infected cell cultures, reactivity against all the 13 ISA virus strains currently available was demonstrated. Using the MAb, a simple, rapid direct immunofluorescent assay for ISA virus detection and titration in 96-well tissue culture plates was developed. Infectivity titrations by this method correlated well with titration by cytopathic effects. The reliability of the assay was demonstrated by close agreement in virus infectivity titres among different assays for the same virus that were performed on the same day and on different days. A method for detection of viral antigen in cryosections from ISA diseased fish is also reported that may prove useful for the diagnosis and control of ISA.